Analyzing Halal Certification Processes, Consumer Behavior, and Regula-tory Landscape in Batam City, Indonesia - Thomas Christian Parray; Hamid Husein Mokhtar (Law and Economics, 2024)
This research aims to provide a comprehensive analysis of halal certification processes, consumer perceptions, and the regulatory landscape in Batam City, Indonesia. The study employs a mixed-methods approach, combining both quantitative and qualitative techniques to achieve a comprehensive understanding of the research objectives. The research design encompasses both primary and secondary data collection methods, including a survey questionnaire, in-depth interviews, and documentary analysis. The findings reveal several key insights, including positive consumer perceptions towards halal certification, challenges faced by businesses in obtaining and maintaining certification, and the fragmented nature of the regulatory landscape.